Can We Eliminate Anaemia from India? - Kapil, Umesh; Gupta, Aakriti (Indian Journal of Community Health, 2018)
Anaemia, as defined by low haemoglobin concentration, is a condition in which the number of red blood cells or their oxygen-carrying capacity is insufficient to meet physiologic needs. It is a major public health problem that affects low, middle and high-income countries. The global prevalence of anaemia is 42.6% in children, 38% in pregnant women and 29.4% in all women of reproductive age. The prevalence of severe anaemia amongst women and children is in the range of 0.9% to 1.5% and is associated with substantially worse health outcomes (1).